PENGARUH MEDIA PUZZLE TERHADAP HASIL BELAJAR SISWA PADA KARAKTERISTIK HIDUP HEWAN DI KELAS IV SDN 106814 TEMBUNG KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG - Andina Halimsyah Rambe; Nurul Delilah Harahap (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This study aims to determine student learning outcomes using puzzle media in Class IV 106814 Tembung students. In this study, the researchers found a problem where there were some students who did not get a score below the KKM, problems were found when conducting initial observations at SDN 106814 Tembung, especially in science subjects. The research was conducted with 4th grade elementary school students on science subjects at SDN 106814 Tembung with the aim of fixing the problems that researchers found and it is hoped that students will be able to develop abilities using puzzle media during the teaching and learning process. This type of research uses a pre-experimental technique with a one group test-post test model, which only involves one class.Keywords: Learning Outcomes, Science, Media Puzzle